The author as cannibal : rewriting in francophone literature as a postcolonial genre, 1969-1995 - Reynolds, Felisa Vergara (University of Nebraska Press, 2021)
After French colonial rule ended, Francophone authors began rewriting narratives from the colonial literary canon. Felisa Vergara Reynolds presents these textual revisions as figurative acts of cannibalism and examines how these literary cannibalizations critique colonialism and its legacy in each author's homeland.